General relativity : a concise introduction - Carlip, Steven (Steven Jonathan), 1953- (UK: Oxford University Press, 2019)
This is a short textbook on general relativity and gravitation aimed at readers with a broad range of interests in physics, from cosmology to high energy physics to condensed matter. The approach is "physics first": readers move quickly to the calculation of observational predictions and only then return to mathematical foundations.--
Gravity as geometry -- Geodesics -- Geodesics in the solar system -- Manifolds and tensors -- Derivatives and curvature -- The Einstein field equations -- The stress-energy tensor -- The weak field approximation -- Gravitational waves -- Black holes -- Cosmology -- The Hamiltonian formalism -- Next steps.
Includes bibliographical references and index.
Keywords: Relativity (Physics); Gravitation; Gravitation; Relativity (Physics)